Tratamentos pré-germinativos em sementes de pitaya (Hylocereus ssp.) para atenuação dos estresses hídrico e salino - Carvalho, Sara Monaliza Costa (2020)
Pitahayas are cacti widely cultivated in tropical and subtropical regions such as Thailand, the Philippines, Vietnam, Malaysia and southern China. However, its cultivation in Brazil is still incipient with small areas located in the state of São Paulo and more recently in semi-arid regions, where water resources are scarce. However, the pitahayas germination process is sensitive to water and saline stresses, primarily in osmotic potentials below -0.2 MPa. Thus, research that seeks to use treatments to minimize the deleterious effects of abiotic stresses is of great relevance at this stage. The objective was to evaluate the efficiency of pre-germinative treatments of pitahaya seeds of white pulp (Hylocereus undatus) and red pulp (Hylocereus costaricensis) to mitigate the effects of water and salt stresses during the germination process. For this, two experiments were conducted, both in a completely randomized design, in a 2 x 6 factorial scheme, corresponding to two species of pitahaya and six pre-germinative treatments, with four replications of 50 seeds. The pre-germinative treatments were: T1 = 0.0 MPa (control); T2 = stress (saline or water); T3 = stress + hydroconditioning; T4 = stress + gibberellic acid; T5 = stress + salicylic acid and T6 = stress + thiametoxan under conditions of water stress or salt stress. The seeds of treatments T3, T4, T5 and T6 were subjected to pre-soaking for 4 hours in hydroconditioning (distilled water), gibberellic acid (150 mg / L), salicylic acid (1μM / L) and thiametoxan (1 mL / Kg seeds), respectively. Then, sowing was carried out on two sheets of blotting paper moistened with PEG 6000 solution, at -0.2 MPa, to simulate water stress (Experiment I) and in NaCl solution at -0.4 MPa, to simulate salt stress (Experiment II). The variables analyzed were the germination percentage, germination speed index, shoot length and primary root length, total dry mass, total soluble sugars and total free amino acids. As for Experiment I, salicylic acid and thiametoxan provided benefits in the development of the species H. costaricensis when observing the results of aerial part and dry matter length gain. Hydroconditioning caused a mitigating effect for seedlings from H. costaricensis, stimulating increases in germination and germination speed index. Gibberellic acid provided better mitigating results to water stress, providing greater germination and germination speed index for both species, in addition to increasing the length of the aerial part of H. undatus seedlings. As for Experiment II, salicylic acid had a mitigating effect on the germination and growth of H. undatus, in addition to increasing the soluble sugar levels in H. costaricensis. The hydroconditioning had a mitigating effect on the germination of H. undatus and favored the growth in dry mass of seedlings. Gibberellic acid stimulated the germination of H. undatus and the growth of H. undatus and H. costaricensis. For H. undatus seeds, this regulator also stimulated an increase in soluble sugar levels